2023
DOI: 10.1007/s10555-023-10126-x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol as sensitizer in colorectal cancer plasticity

Abstract: Despite tremendous medical treatment successes, colorectal cancer (CRC) remains a leading cause of cancer deaths worldwide. Chemotherapy as monotherapy can lead to significant side effects and chemoresistance that can be linked to several resistance-activating biological processes, including an increase in inflammation, cellular plasticity, multidrug resistance (MDR), inhibition of the sentinel gene p53, and apoptosis. As a consequence, tumor cells can escape the effectiveness of chemotherapeutic agents. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 328 publications
0
7
0
Order By: Relevance
“…Additionally, resveratrol has recently received attention as anti-adipogenic phytonutrient for the prevention and management of obesity and obesity-related metabolic syndrome [ 150 ], highlighting its potential role in the prevention of numerous chronic inflammatory diseases ( Figure 6 ). The natural polyphenol is also a promising adjuvant approach to chemosensitization in the setting of conventional cancer therapies to prevent therapy resistance and reduce systemic side effects [ 151 ]. The great potential of the phytopharmaceutical is illustrated in particular by its property to act both catabolically, as on BC [ 56 ], and anabolically, as on OP [ 149 ].…”
Section: Resveratrolmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, resveratrol has recently received attention as anti-adipogenic phytonutrient for the prevention and management of obesity and obesity-related metabolic syndrome [ 150 ], highlighting its potential role in the prevention of numerous chronic inflammatory diseases ( Figure 6 ). The natural polyphenol is also a promising adjuvant approach to chemosensitization in the setting of conventional cancer therapies to prevent therapy resistance and reduce systemic side effects [ 151 ]. The great potential of the phytopharmaceutical is illustrated in particular by its property to act both catabolically, as on BC [ 56 ], and anabolically, as on OP [ 149 ].…”
Section: Resveratrolmentioning
confidence: 99%
“…Numerous in vitro and in vivo studies have demonstrated the anti-proliferative, pro-apoptotic, anti-angiogenic, and chemosensitizing effects of resveratrol on various types of cancer, including BC [ 151 ], by attenuating pro-inflammatory mediators through the modulation of NF-κB and STAT3 signaling in BC cells ( Figure 7 ) [ 157 , 158 ].…”
Section: Resveratrolmentioning
confidence: 99%
“…Furthermore, the anti-cancer properties of RSV against colorectal cancer have been proven through many clinical trials. In one explanation, RSV acts as a chemosensitizer that modifies many subcellular pathways (p38-MAPK, Akt/STAT3, IL-6/JAK, and other signaling pathways) altering angiogenesis, apoptosis, metastasis, and transcription factors (RSV inhibits the NF-kB and its promoted end-proteins) suppressing cancer plasticity [ 59 , 60 ]. In lung cancer as well, signaling pathways involved in cancer progression such as the mTOR, PI3K/Akt, Wnt/B-catenin are targeted by RSV as a mechanism to reduce the cancer burden [ 61 ].…”
Section: Structure and Therapeutics Of Resveratrolmentioning
confidence: 99%
“…[56] Moreover, several studies using a mouse xenographic model demonstrated, in addition to the chemosensitizing effect, an additional radiosensitizing effect against colorectal cancer cells. [57,58]…”
Section: Polyphenols and Colorectal Cancermentioning
confidence: 99%